Insect venom phospholipases A1 and A2: Roles in the envenoming process and allergy - Perez-Riverol, Amilcar [UNESP] (2019)
Insect venom phospholipases have been identified in nearly all clinically relevant social Hymenoptera, including bees, wasps and ants. Among other biological roles, during the envenoming process these enzymes cause the disruption of cellular membranes and induce hypersensitive reactions, including life threatening anaphylaxis. While phospholipase A2 (PLA2) is a predominant component of bee venoms, phospholipase A1 (PLA1) is highly abundant in wasps and ants. The pronounced prevalence of IgE-mediated reactivity to these allergens in sensitized patients emphasizes their important role as major elicitors of Hymenoptera venom allergy (HVA). PLA1 and -A2 represent valuable marker allergens for differentiation of genuine sensitizations to bee and/or wasp venoms from cross-reactivity. Moreover, in massive attacks, insect venom phospholipases often cause several pathologies that can lead to fatalities. This review summarizes the available data related to structure, model of enzymatic activity and pathophysiological roles during envenoming process of insect venom phospholipases A1 and -A2.